The Impact of Gender and Sociodemographic Characteristics on Dentists' Practice Patterns, Employment Status, and Workforce Participation. (15th September 2021) - Langelier, Margaret; Moore, Jean; Surdu, Simona
Abstract : Research Objective: Gender diversification is rapidly occurring within the dental profession. Gender differences in practice choice (eg, employment vs practice ownership) and practice participation (eg, part‐time vs full‐time work hours) have been reported. It is important to understand how changes in the delivery system including workforce participation and preferences might impact the availability of services especially for underserved populations. The objectives of this study were to evaluate the variation in practice preferences among female and male dentists and to assess potential associations with socioeconomic and family factors. Study Design: The current study used data from the Census Bureau's American Community Survey (ACS). The variables extracted describe dentists' sociodemographic characteristics including gender, age, race/ethnicity, presence of children or elders in the household, household income, and marital status, as well as dental practice characteristics such as employment status, practice setting, and work hours. Population Studied: The 5‐year Public Use Microdata Sample data (2014–2018) from the ACS were utilized. Person‐level data collected through the questionnaire contain demographic, social, and economic information. The analytical sample consisted of 9993 dentists and 520, 925 people living in the dentists' households. Survey data was weighted to generate unbiased estimates representative for the US population. Principal Findings: Female dentists were younger (mean 43.3 years vs 53.6; P < 0.001), more racially and ethnically diverse (58.1% vs 78.6% White, non‐Hispanic; P < 0.001), and proportionally more foreign‐born (35.2% vs 17.7%; P < 0.001) compared to male dentists. Female dentists were more likely to report being employed (55.1% vs 34.8%; P < 0.001) or working part‐time (less than 30 hours per week) in dental practice (15.5% vs 11.0%; P = 0.001) than male dentists. Female dentists with children were more likely to report being an employee (64.3% vs 52.8%; P < 0.001) and working part‐time (19.5% vs 14.3%; P < 0.001) compared to female dentists without children in their care. Proportionally fewer female dentists left the workforce (ie, retired) in the past 12 months than male dentists (2.4% vs 3.6%; P = 0.002). Average income in the past 12 months was significantly lower (P < 0.001) for female dentists (mean = 141, 267; 95% Confidence Interval [CI] = 135, 452 ‐147, 082) compared to male dentists (mean = 185, 923; 95% CI = 135, 452–147, 082). Conclusions: The data indicate that the dental workforce is diversifying in gender and by race/ethnicity. The data about dental practice by gender is consistent with the current literature; female dentists were significantly more likely to be employed than to be self‐employed/a practice owner. This preference is consistent with evolving practice models including consolidations of smaller practices into group practices and changing business models for the profession. The wage gap by gender, which has been previously researched, is notable and difficult to explain. Implications for Policy or Practice: The percentage of women entering and graduating from dental schools has increased over recent years achieving equity in numbers in dental schools in the US. Differences in employment status and workforce participation by gender are important preferences that should be monitored over time to ascertain if availability of services is affected by these trends. Primary Funding Source: Health Resources and Services Administration.